Early application of nanocarbon suspension in gastric cancer patients enhances postoperative lymph node detection - Sheng Li; Xiaoli Chen; Xiaoyu Yang; Zhiyao Chen; Jiahui Xiong; Yanting Lin; Liang Chen; Shiyi Lu; Lijing Lin; Jianan Chen; Manbian Lin; Xiaoliang Cai (World Journal of Surgical Oncology)
Abstract Background This retrospective cohort study explores the association between the interval of nanocarbon application before surgery and the detection of postoperative lymph nodes in patients undergoing gastric cancer surgery. Methods This retrospective study included eligible patients diagnosed with T1-3NanyM0 gastric cancer at Fuzhou Traditional Chinese Medicine Hospital between March 1, 2020, and March 31, 2023, based on predefined inclusion criteria. Participants were grouped according to the timing of nanocarbon suspension application: either on the same day as surgery or at least 3 days prior. We compared clinicopathological characteristics between these two groups. Results Our findings indicate a significant increase in the number of lymph nodes detected postoperatively in patients who received nanocarbon suspension at least 3 days before surgery compared to those who received it on the same day (26.33 ± 3.42 vs. 30.41 ± 2.16, P < 0.05). Early nanocarbon suspension application was found to be safe, with no observed adverse effects or complications. Conclusions Early application of nanocarbon suspension may enhance lymph node detection, potentially allowing for more accurate pathological staging. This approach could provide valuable guidance for subsequent comprehensive anti-tumor therapy.